Cationic photopolymerization kinetics of neat coating formulations involving poly(propylene glycol) diglycidyl ether and glycerol diglycidyl ether - Harikrishna, Reghunathan (Journal of Thermal Analysis and Calorimetry, 2015)
Kinetic analysis of formulations based on poly(propylene glycol) diglycidyl ether and glycerol diglycidyl ether was carried out using photodifferential scanning calorimeter. The effects of formulation monomer ratios at different temperatures were studied as photocalorimetric optimization studies of formulation ratios involving diglycidyl ethers are less reported. The nature of cure was found to depend more on the in situ physical parameters rather than on the mechanism of the reaction. The variations in the observed kinetic parameters can be related to interplay of mobility of reactive species, distance of counter ion and the diffusional restrictions. The final conversion was found to increase with increase in poly(propylene glycol) diglycidyl ether content, while the thermal stability increased with an increase in glycerol diglycidyl ether content. Autocatalytic kinetic model was also evaluated, and the system underwent early gelation. The studies show that the intermediate formulations are promising compositions for surface-coating applications.
Keywords: Coatings; Diglycidyl ether; kinetics; PhotoDSC; Photopolymerization